2012
DOI: 10.1029/2012jc007933
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the amount of cesium‐137 released into the Pacific Ocean after the Fukushima accident and analysis of its dispersion in Japanese coastal waters

Abstract: Numerical modeling was used to provide a new estimate of the amount of 137Cs released directly into the ocean from the Fukushima Daiichi nuclear power plant (NPP) after the accident in March 2011 and to gain insights into the physical processes that led to its dispersion in the marine environment during the months following the accident. An inverse method was used to determine the time‐dependent137Cs input responsible for the concentrations observed at the NPP's two liquid discharge outlets. The method was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 34 publications
4
65
0
1
Order By: Relevance
“…Using the numerical-model-based average age of 27 days, this value increases to 16 PBq. Our direct discharge estimated range is significantly greater (∼ 2-5 times) than an early (3.5 PBq, Tsunume et al, 2011) and more recent estimate of direct ocean release (5.1-5.5 PBq, Estournel et al, 2012), but generally consistent with the estimate (16.2 ± 1.6 PBq) obtained by Rypina et al (2013), and within the range of 12-41 PBq reported by Bailly du Bois et al (2012). The variability in total direct ocean discharges of Cs is due to the large uncertainties of the different transport and inversion processes used by each study and lack of spatially distributed observations in the surrounding region, which leads to uncertainty in the ocean inventory of Cs at any given point in time.…”
Section: Discussionmentioning
confidence: 84%
“…Using the numerical-model-based average age of 27 days, this value increases to 16 PBq. Our direct discharge estimated range is significantly greater (∼ 2-5 times) than an early (3.5 PBq, Tsunume et al, 2011) and more recent estimate of direct ocean release (5.1-5.5 PBq, Estournel et al, 2012), but generally consistent with the estimate (16.2 ± 1.6 PBq) obtained by Rypina et al (2013), and within the range of 12-41 PBq reported by Bailly du Bois et al (2012). The variability in total direct ocean discharges of Cs is due to the large uncertainties of the different transport and inversion processes used by each study and lack of spatially distributed observations in the surrounding region, which leads to uncertainty in the ocean inventory of Cs at any given point in time.…”
Section: Discussionmentioning
confidence: 84%
“…In the days-weeks following the reactor meltdowns, dissolved 137 Cs activities reached >60 × 10 6 Bq·m −3 in the ocean closest to the FDNPP (5). Numerical modeling demonstrated that a net southward flowing coastal current transported this highly radioactive seawater along the shoreline (11). We hypothesize that seawater intrusion, driven in part by waves and tides (12)(13)(14)(15), led to the storage of 137 Cs by adsorption onto beach sands.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last two years there have been a number of numerical modeling studies aimed at assessing the aftermath of the Fukushima disaster (e.g., Tsumane et al, 2011Tsumane et al, , 2013Kawamura et al, 2011;Estournel et al, 2012;Miyazawa et al, 2012;Masumoto et al, 2012;Bailly du Bois et al, 2012). Forward numerical models have allowed simulation of the spread of radioactive waters into the ocean.…”
Section: Modeling the Spreading Of 137 Csmentioning
confidence: 99%